SURVEY KEPUASAN LAYANAN AKADEMIK FAKULTAS HUKUM UNIVERSITAS TANJUNGPURA - Erwin; Mega Fitri Hertini; Rachmawati; Sri Widiyastuti; Alhadiansyah; Edy Suasono; Vera Puji Lestari (Ganesha Law Review, 2023)
The main objective of this research is to map the existence and implementation or implementation of academic service satisfaction during the Covid-19 Pandemic, especially at the Faculty of Law, University of Tanjungpura both in terms of results, processes, and effectiveness. It is hoped that this research will provide theoretical benefits in enriching thoughts and concepts about academic services, as well as practical benefits for students, lecturers, education staff and faculty leaders for feedback and improving various academic services. The results of this study indicate that in terms of the aspects of reliability, responsiveness, assurance (treatment of students), empathy (understanding of student interests), information systems (student information systems) at the Faculty of Law, University of Tanjungpura in terms of academic services quite satisfactory.